MEASURING THE EFFECT OF THE ECONOMIC ACTIVITY RATE ON THE UNEMPLOYMENT RATE USING PANEL DATA MODELS - Jassim N.Hussain, Zainab Kadhum Mezher, Marwa Haider Ghazi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In this research, the statistical method, Panel Data Models, was employed to measure the strength of the relationship between variables and analyze them, and to show the effect of the explanatory variable (X), which represents economic activity on the dependent variable (Y), which represents the unemployment rate in some Iraqi provinces.(Waist, Kerbala, Babylon, Najaf) for the period from (2005-2019),As the two variables were represented graphically to know the trend of the phenomenon and determine its events, and among the most important conclusions that were reached is that the summative regression model (PRM) is the best in that it is the most appropriate in representing the inverse relationship between the variable of unemployment rate and the variable of economic activity. In addition to the presence of a significant impact of the variable of the unemployment rate and the variable of economic activity, the more jobs (economic activity) the unemployment rate will decrease. On this basis, a set of recommendations have been drawn up to take the necessary care and develop the phenomenon studied, the most prominent of which is the expansion of the study sample (number of sections) to include More than one Iraqi governorates, and the need for the Ministry of Labor to pay attention to creating job opportunities in order to contribute significantly to the elimination of unemployment.